Usia Tingkat Pendidikan Dan Pengetahuan Antenatal Care IbuPrimigravida Dalam Kecemasan Menghadapi Persalinan - Yainanik, Yainanik; , Dr. Nisa Rachmah N.A., M.Si, Psi (2017)
The first pregnancy for a woman (primigravida) is a new problem that can bring anxiety in her life. Disruptive anxiety is a response to future threats imagined not the real danger of the present. The anxiety of primigravida mother is influenced by many things such as pregnant mother who is young age, low education level and lack of knowledge about antenatal carenya.This study aims to examine the correlation (1) age with anxiety, (2) education level with anxiety (3) antenatal knowledge with anxiety and (4) age, education level and antenatal care knowledge with anxiety. This study examined the first 60 pregnant women in the working area of Puskesmas Jaten subdistrict with purposive sampling. The research instrument used the Hamilton Anxiety Rating Scale (HARS) questionnaire and 20 antenatal care knowledge questions by using Kendall correlation statistics test statistic; Double correlation test and partial correlation test with a significance level of 95% or α = 0.05. The result of data analysis to 60 respondents stated that there is a significant correlation between age variable with anxiety, education level with anxiety, antenatal care knowledge with anxiety and age, education level and antenatal care knowledge with anxiety facing childbirth, with contribution of 25,7%. Conclusion (1) there was a significant relationship of age with anxiety, (2) there was a significant relationship education level with anxiety, (3) there was significant relationship antenatal care knowledge with anxiety and (4 ) There is a significant relationship of age, education level and antenatal care knowledge with anxiety. The implications of age, level of education, and knowledge of antenatal care in psychological aspects affect the anxiety so it needs to be considered to minimize the level of anxiety.